Analisis Kemampuan Kolaborasi Siswa SMP dalam Pembelajaran Ekologi melalui Penggunaan Video Interaktif Berbasis Lumi - Rasydianah, Rasydianah; Sabar Nurohman; Wilujeng, Insih; Rahmawati, Laifa; Winarto, Winarto; Firdaus, Firdaus (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze junior high school students’ collaboration skills in ecology learning through the use of Lumi-based interactive videos. Collaboration is recognized as a critical 21st-century skill that needs to be cultivated in science education. The research employed a pre-experimental method with a one-shot case study design, involving no control group or pre-test. The participants were 20 seventh-grade students from MTsN 1 Majene, selected through convenience sampling. The intervention was conducted over two class meetings using a 12-minute interactive video integrated with digital worksheets (LKPD). Data were collected using a collaboration skills questionnaire and a behavioral observation sheet. The results revealed that students’ collaboration ability was in the “High” category, with an average score of 78.75. The shared responsibility indicator showed strong consistency between self-assessment and observation (2.82% difference), while the flexibility indicator exhibited signs of overestimation (5% gap), and the diversity indicator showed a notable disparity between self-perception and actual behavior (6.25% gap). These findings indicate that Lumi interactive video media effectively supports the development of collaboration skills and highlight the need for differentiated instruction. The study offers practical insights into integrating digital literacy with collaborative pedagogy, in alignment with the Pancasila Student Profile framework